2017
DOI: 10.3897/zoologia.34.e13732
|View full text |Cite
|
Sign up to set email alerts
|

Differences between caves with and without bats in a Brazilian karst habitat

Abstract: ABSTRACT. Since bats shelter in roosts during their period of diurnal inactivity, the quality and availability of roosts are important aspects of their ecology. Karst areas have great potential for the availability of day roosts, since they form caves, which serve as bat shelters. Here we characterize the caves used by bats in a preserved karst area of Southeastern Brazil. Using logistic regression analysis we identified the cave characteristics that influence bat occupation. Sixty-six caves were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
4
4
0
3
Order By: Relevance
“…In Puerto Rico, for example, only 31% of the caves in the National Speleology database are used as roosts [49]. A similar study in Brazil shows that only about half of the observed caves had bats [50]. We also found that in combination, all caves harbor a total of 20 species.…”
Section: Discussionsupporting
confidence: 70%
“…In Puerto Rico, for example, only 31% of the caves in the National Speleology database are used as roosts [49]. A similar study in Brazil shows that only about half of the observed caves had bats [50]. We also found that in combination, all caves harbor a total of 20 species.…”
Section: Discussionsupporting
confidence: 70%
“…For example, our analysis confirmed this by the temperature range and the maximum temperature variables, which had the highest model contribution towards the mid-end hibernation period, limiting optimal habitat patches within hotter and more stable temperatures for thermophile bat species, such as Rhinolophus spp. Roost length was also relevant for bat abundance and species diversity in all of our studied subterranean environments, as Torquetti et al [19] also found, and was linked to larger patches of stable temperatures, therefore a wider selection of optimal habitats. At the beginning of the hibernation period most species and populations were corelated with smaller distances from the entrances, because they use the climatic variability to exit daily torpor and feed in optimal conditions [78], but during the colder winter…”
Section: Ecology Of the Focal Bat Speciessupporting
confidence: 76%
“…The maternity period usually requires proximity to the entrances, where temperatures are more suitable for nursing [19], except for the case of temperature inversions, where the colonies can be formed even in deep sectors of the roosts (SE 10), as our models also predicted. Often smaller sites with exterior hot air influxes are preferred [19].…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…In contrast, our study found a more than three times higher average (12.9 °C) suggesting good adaptation of the vampire bat to the climatic conditions in the study region. It is known that D. rotundus does not hibernate, but lives long periods in caves, in tree holes, under bridges and in old buildings during the day where the microclimate differs from that of the general environment (Torquetti et al, 2017). In fact, it has been reported that the factors that most contribute to the spatial distribution of rabies in livestock are temperature and precipitation as these variables offer a micro-climate inside bat refuges that favour the distribution of possible infected vampire bats with the rabies virus (Bárcenas-Reyes, 2013;Bárcenas-Reyes et al, 2015;de Thoisy et al, 2016;Hayes and Piaggio, 2018).…”
Section: Discussionmentioning
confidence: 99%